Responses of growth and leaf phenolics in European aspen (Populus tremula) to climate change during juvenile phase change - Nissinen, Katri; Virjamo, Virpi; Randriamanana, Tendry; Sobuj, Norul; Sivadasan, Unnikrishnan; Mehtätalo, Lauri; Beuker, Egbert; Julkunen-Riitto, Riitta; Nybakken, Line (NRC Research Press, 2017)
In trees, the change from juvenile to adult vegetative phase can last for years. In Populus tremula L., this phase change is characterized by a morphological change in leaf shape, as leaves in the seedling phase typically are sharp-tipped, while saplings and trees have round-tipped leaves. In an open-field experiment, we studied the separate and combined effects of enhanced temperature and UVB radiation on 2-year-old P. tremula plantlets undergoing phase change. The concentration of salicylates was higher in the seedling-phase plants than in tree-type plants. In contrast, the concentration of condensed tannins was higher in the tree-type plants but only under ambient temperature. Enhanced temperature increased growth of the plants and the concentration of some salicylate compounds, and it decreased concentrations of flavonoids, phenolic acids, and condensed tannins. In addition, in the seedling-phase plants, the severity of rust infections decreased and herbivore damage increased under warming. The effects of enhanced UVB radiation were weaker, as concentrations of only two flavonoid compounds increased under enhanced UVB radiation. Based on our results, climate change may have a moderate delaying effect on the physiological development of both sexes of P. tremula, which may lead to lowered performance in their normal habitat in the future.
Keywords: secondary compounds; UVB; sex differences; temperature; infestation